Botanical relics of a lost landscape: herborising ‘upon the Cliffs about the Pharos’ in Genoa, March 1664 - Bruzzone, Rafaella; Watkins, Charles; Balzaretti, Ross; Montanari, Carlo (Taylor & Francis, 2018)
This paper uses approaches derived from historical ecology to show how knowledge can be gained about the historical and cultural value of neglected urban landscapes. We study the area around Genoa’s lighthouse and consider the long-term survival of individual plant species and some implications for landscape conservation. We examine topographical representations over the last 500 years to establish the landscape context of the lighthouse. We then analyse the records of plants collected by two English naturalists of the seventeenth century, John Ray and Francis Willughby, and demonstrate how the plants were identified and documented. We survey the current vegetation to establish whether any species identified in 1664 still grow at the site. This exploration of botanical ancestry at a local scale makes it possible to demonstrate cultural–historical values of the lighthouse rocks and their vegetation which should be considered as part of the cultural heritage of the city of Genoa.